Enhanced elastic and optical attributes of boro-telluro-dolomite glasses: role of CeO2 doping - Bulus, Ibrahim (Elsevier Ltd., 2019)
Improvement of elastic and optical properties of rare earth ions doped glasses via the amalgamation of synthetic glass formers with natural mineral modifier became a new strategy to achieve novel glass based optical devices. Inspired by this idea, we prepared some new types of CeO2 doped boro-tellurite-dolomite (BTD) glasses of composition (35-x)B2O3–30TeO2-20Dp-15Dm-xCeO2 (where 0≤x≤ 2.0 mol%, Dm: dolomite marble and Dp: dolomite pebble) by standard melt-quenching method and characterized. The role of changing CeO2 concentration on the structural, elastic and optical traits of the proposed glasses was examined. Also, direct and indirect band gap energies, Urbach energies and refractive indices of glasses were evaluated using Tauc, absorption spectrum fitting (ASF) and derivation of absorption spectrum fitting (DASF) methods. Amorphous nature of the as-quenched samples was verified from XRD pattern and SEM image showed the homogeneous disordered surface. EDX spectra disclosed the right elemental traces in the prepared glasses. The N4 ratio calculated from the FTIR spectra revealed that the inclusion of CeO2 into the BTD network indeed favoured the conversion of BO3 to BO4 structural units. Besides, the ultrasonic velocities and elastic moduli were reduced with the increase in CeO2 contents. Complete absence of any peak in the optical absorption spectra validated the existence of Ce4+ within glasses. Moreover, the absorption coefficient of prepared glasses was significantly enhanced and the absorption edge was red shifted (from 400 nm to 500 nm) with the increase in CeO2 doping. Proposed glass compositions may be beneficial for future research and development on optical filter in photonic devices.